(untitled) (Research, Society and Development, 2024)
Carbohydrates are one of the most important groups of biomolecules for living beings due to their structural and functional variety. One of these carbohydrates is alginate, a natural polymer with a wide range of applications in the food, cosmetic and biotechnology industries. In the latter, the application of alginate is mainly due to its ability to form bonds with divalent cations, producing matrices that retain a large amount of water and drugs in their structure. In this sense, the objective of this work was to present a biotechnological application of carbohydrates to high school/technical students through the preparation of alginate spheres as a drug carrier system. The work consisted of an experimental activity in the Biology Laboratory of the Federal Institute of Education, Science and Technology of Pernambuco – Campus Barreiros, with students from the Agricultural Technician and Food Technician courses. At the end of the activities, the work was evaluated as Good, Very Good and Excellent by the majority of participants. Therefore, from this perspective, the proposed activity was considered successful. It is worth noting that the focus of this work was not the mathematization of the concepts taught; but rather, the processes of construction, appropriation and interpretation of this knowledge.